Developing Nusa Lembongan As A Destination For 5A-Based Tourism Events - I Gede Sumadi; Ni Kadek Swandewi; Ni Wayan Purnami Rusadi (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
Event-based tourism has become a key strategy in destination development. Nusa Lembongan, with its unique natural beauty, has significant potential for development as a tourism event destination. This analysis aims to assess the potential and challenges of this development using the 5A model framework (attraction, accessibility, amenities, activities, and ancillary services). The research uses observation, interviews, documentation, literature review, and data analysis. The findings of this research analysis shows that Nusa Lembongan excels in Attractions and Activities, with its underwater beauty, beaches, and mangrove forests ideal for ecotourism and water sports-based events. However, the island still faces significant challenges in the pillars of accessibility (limited sea transportation and road infrastructure), Amenities (lack of large-capacity MICE venues), and supporting services (limited medical facilities and waste management systems). Overall, Nusa Lembongan has strong potential to become a thematic event destination, but its development requires strategic improvements in infrastructure and supporting services. It is recommended to invest in the development of specific event facilities, improve sustainable environmental management, and promote events that are in harmony with the island's natural character, such as eco-tourism and wellness retreats.